Racism as a public health issue in environmental health disparities and environmental justice: working toward solutions - Sharon Beard; Kenda Freeman; Maria L. Velasco; Windy Boyd; Toccara Chamberlain; Alfonso Latoni; Denise Lasko; Ruth M. Lunn; Liam O’Fallon; Joan Packenham; Melissa M. Smarr; Robin Arnette; et al. (Environmental Health, 2024)
Abstract Background Environmental health research in the US has shown that racial and ethnic minorities and members of low-socioeconomic groups, are disproportionately burdened by harmful environmental exposures, in their homes, workplace, and neighborhood environments that impact their overall health and well-being. Systemic racism is a fundamental cause of these disproportionate exposures and associated health effects. To invigorate and inform current efforts on environmental justice and to raise awareness of environmental racism, the National Institute of Environmental Health Sciences (NIEHS) hosted a workshop where community leaders, academic researchers, and NIEHS staff shared perspectives and discussed ways to inform future work to address health disparities. Objectives To share best practices learned and experienced in partnerships between academic researchers and communities that are addressing environmental racism across the US; and to outline critical needs and future actions for NIEHS, other federal agencies, and anyone who is interested in conducting or funding research that addresses environmental racism and advances health equity for all communities. Discussion Through this workshop with community leaders and researchers funded by NIEHS, we learned that partnerships between academics and communities hold great promise for addressing environmental racism; however, there are still profound obstacles. To overcome these barriers, translation of research into plain language and health-protective interventions is needed. Structural changes are also needed in current funding mechanisms and training programs across federal agencies. We also learned the importance of leveraging advances in technology to develop creative solutions that can protect public health.